Bal??le As A Ritual To Inherit Banggai Cultural Values - Samatan, Nuriyati; Wahyudin; Ariandi Putra; Robingah (International Journal of Advanced Multidisciplinary, 2023)
This research aims to examine Baleele culture as a value inheritance ritual in Banggai culture. This research is qualitative, using an ethnographic approach with the following steps: [1] Determining the object of ethnographic research; [2] Identifying and determining the location of the cultural group; [3] Selecting the cultural theme of the cultural group; [4] Determining the type of ethnography; [5] Collecting information; [6] Writing research results. The result found that Baleele is a form of ritual communication carried out at a certain time, ahead of the "Big Ritual" of Banggai custom, namely the Mabangun Tunggul Ritual, held every 6 years. Baleele is one of the rituals that takes place three nights before the Mabangun Tunggul Ritual. The Banggai people strongly believe in the advice delivered, and consider the process as something sacred, valuable, for themselves, their families and the Banggai community as a whole.